Expression of tissue factor in canine mammary tumours and correlation with grade, stage and markers of haemostasis and inflammation. (28th March 2014) - Andreasen, E. B.; Nielsen, O. L.; Tranholm, M.; Knudsen, T.; Kristensen, A. T.
Abstract: Tissue factor (TF) expression in human cancers has been associated with a procoagulant state and facilitation of metastasis. This study was conducted in order to evaluate if TF was expressed in canine mammary tumours. Forty epithelial mammary tumours from 28 dogs were included. TF expression of the tumours was evaluated by immunohistochemistry using a polyclonal antibody against recombinant canine TF. In addition, thromboelastography, haemostatic and inflammatory parameters were evaluated in the patients. TF was recognized in 44% of benign and 58% of malignant tumours. TF localized to the cytoplasmic membrane of neoplastic luminal epithelial cells and/or diffusely in the cytoplasm. No association was found between TF expression and stage or grade of disease. A significant association between TF expression and antithrombin and plasminogen was found, and extensive TF expression was seen in a lymph node metastasis classified as anaplastic mammary carcinoma from a dog with concomitant disseminated intravascular coagulation (DIC).